Effect of consumer ethnocentrısm and servıce qualıty perceptıon on satısfactıon: a cross cultural study on fast food ındustry - Younas, Muhammad Ghufran (My University, 2016)
TÜKETİCİ ETHNOCENTRISM KÜLTÜRÜ VE HİZMET KALİTESİ ALGISININ FAST FOOD SEKTÖRÜNDEKİ MÜŞTERİ MEMNUNİYETİNE ETKİSİ Dünya ekonomisinin giderek büyümesi ile çok uluslu şirketler kendi ulusal ve siyasal sınırlarının ötesine geçerek ürün ve servislerini pazarlamaya başlamışlardır.Müşteri odaklı pazar araştırması yaklaşımında ürün deneyimleri ve kültürlerarası farklılık rekabet avantajı için ayırt edici faktörler olarak karşımıza çıkmaktadır.Bu faktörlerin rekabet gücü yüksek piyasalarda, karar verme süreçleri için nasıl hesaplanacağına dair bilgileri sınırldır.Etkili pazarlama stratejisi için müşteri memnuniyeti ve tüketici etnocentrizmi davranışları arasındaki ilişkinin araştırılması çok önemlidir.Bu çalışmanın amacı, batı kültüründen (Almanya), doğu kültüründen (Pakistan) ve hem doğu hem batı kültür karışımından (Türkiye) tüketicileri karşılaştırarak tüketici etnik eğilimlerini belirlemektir. Tüketiciler ihtiyaçları için neyin iyi seçim olduğunu farklı kültürel yönelimleri ile çeşitli görüşlere sahiptirler.Hizmet kalitesi boyutları için mevcut müşteri beklentisi ve algısı tüketici etnik eğilimlerinin etkisi ile birlikte ithal edilen ürünler için araştırılmıştır.Shimp & Sharma (1987) CETSCALE, tüketici etnik eğilimleri doğrulamak için, Hofstede'nin (2001) kültürel yönelimin boyutları ise ülkelerin kültürüne ilişkin literatürüne temel sağlamak için kullanılır.Fast food restoran hizmet kalitesi Stevens, Knutson ve Patton (1995) tarafından geliştirilen DINESERV methodu ile ölçümlenmiştir.Bu araştırma gelişmiş ülkelerden daha az gelişmiş ülkelere hizmet kalitesi algısı, beklentisi ve memnuniyeti açısından tüketici etnik eğilimleri ile ilgili bakış açılarını oluşturmaktadır. Bu araştırma fast-food sektöründe müşteri memnuniyetini etkileyebilecek hizmet kalitesi boyutlarını belirler. rel Boyutlar, Tüketici etnik eğilimleri, Hizmet Kalitesi, Pazarlama İletişimleri, Memnuniyet

EFFECT OF CONSUMER ETHNOCENTRISM AND SERVICE QUALITY PERCEPTION ON SATISFACTION: A CROSS CULTURAL STUDY ON FAST FOOD INDUSTRY With the increasing growth of the world economy multinational companies have started marketing their products and services beyond their national and political boundaries. Marketing research with customer centered approach signifies product experiences and cross cultural difference as a distinguishing techniques for competitive advantage. In highly competitive markets, Information regarding how these factors are accounted for during decision making process is still limited. Investigating the relationship between customer satisfaction and consumer ethnocentrism behaviours making styles is very important for making the effective marketing strategy. The purpose of this study to determine consumer ethnocentric tendencies by comparing the consumers from a western culture (Germany) with ones from an eastern culture (Pakistan) and a blend of western and eastern cultural (Turkey). Consumers have diverse cultures orientations and different views of what constitutes as “good fit” for their needs. Service Quality dimensions and service quality gap present between customer perceptions and expectation is explored for the imported products along with the effect of consumer ethnocentric tendencies. Shimp & Sharma (1987) CETSCALE is used for validating consumer ethnocentric tendencies while Hofstede’s (2001) dimensions of cultural orientation provide the literature base regarding culture of countries under study. Service quality in fast food restaurant scenario is measured through modified DINESERV instrument originally developed by Stevens, Knutson and Patton (1995). The study generates insights regarding consumer ethnocentric tendencies that reflect deviation from more developed countries to less developed countries in terms of service quality perception, service quality expectation and satisfaction. The study also provide service quality dimension in fast food industry that can effect customer satisfaction. Cross Culture Differences, Cultural Dimensions, Consumer Ethnocentric Tendencies, Service Quality, Marketing Communications, Satisfaction
Keywords: Müşteri memnuniyeti; Pazarlama; Üretim yönetimi